A pangenome and pantranscriptome of hexaploid oat - Raz Avni; Nadia Kamal; Lidija Bitz; Eric N. Jellen; Wubishet A. Bekele; Tefera T. Angessa; Petri Auvinen; Oliver Bitz; Brian Boyle; Francisco J. Canales; Craig H. Carlson; Brett Chapman; et al. (Nature, 2026)
Abstract Oat grain is a traditional human food that is rich in dietary fibre and contributes to improved human health 1,2 . Interest in the crop has surged in recent years owing to its use as the basis for plant-based milk analogues 3 . Oat is an allohexaploid with a large, repeat-rich genome that was shaped by subgenome exchanges over evolutionary timescales 4 . In contrast to many other cereal species, genomic research in oat is still at an early stage, and surveys of structural genome diversity and gene expression variability are scarce. Here we present annotated chromosome-scale sequence assemblies of 33 wild and domesticated oat lines, along with an atlas of gene expression across 6 tissues of different developmental stages in 23 of these lines. We construct an atlas of gene-expression diversity across subgenomes, accessions and tissues. Gene loss in the hexaploid is accompanied by compensatory upregulation of the remaining homeologues, but this process is constrained by subgenome divergence. Chromosomal rearrangements have substantially affected recent oat breeding. A large pericentric inversion associated with early flowering explains distorted segregation on chromosome 7D and a homeologous sequence exchange between chromosomes 2A and 2C in a semi-dwarf mutant has risen to prominence in Australian elite varieties. The oat pangenome will promote the adoption of genomic approaches to understanding the evolution and adaptation of domesticated oats and will accelerate their improvement.